2021
DOI: 10.3390/cancers13051046
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PVT1 Exon 9 Re-Expresses Claudin 4 Protein and Inhibits Migration by Claudin—Low Triple Negative Breast Cancer Cells

Abstract: PVT1 is a long non-coding RNA transcribed from a gene located at the 8q24 chromosomal region that has been implicated in multiple cancers including breast cancer (BC). Amplification of the 8q24 chromosomal region is a common event in BC and is associated with poor clinical outcomes. Claudin–low (CL) triple negative breast cancer (TNBC) is a subtype of BC with a particularly dismal outcome. We assessed PVT1 exon 9 expression in the T47D estrogen receptor positive BC cell line, and in the MDA MB 468 and MDA MB 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Many of these lncRNAs showed association with other RNAs. CASC2 acts as a tumor suppressor and potentially as a competing endogenous RNA for miR-21, and plays important role in IDH1 wild type glioma pathogenesis and patients' outcomes [51] , LINC00265 can promote colorectal tumorigenesis via ZMIZ2 and USP7-mediated stabilization of beta-catenin [52] , and PVT1 exon 9 regulates claudin 4 expression and migration in CL TNBC cells, and may have clinical implications in CL TNBC [53] . A pan-cancer analysis showed that some were also deregulated in other cancer types ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these lncRNAs showed association with other RNAs. CASC2 acts as a tumor suppressor and potentially as a competing endogenous RNA for miR-21, and plays important role in IDH1 wild type glioma pathogenesis and patients' outcomes [51] , LINC00265 can promote colorectal tumorigenesis via ZMIZ2 and USP7-mediated stabilization of beta-catenin [52] , and PVT1 exon 9 regulates claudin 4 expression and migration in CL TNBC cells, and may have clinical implications in CL TNBC [53] . A pan-cancer analysis showed that some were also deregulated in other cancer types ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A year later, Levine et al. [ 145 ] suggested that PVT1 exon 9 may regulate BC cell migration by reducing claudin 4 expression.…”
Section: Role Of Pvt1 In Various Human Tumorsmentioning
confidence: 99%
“…Subsequently, El-Fattah et al [144] revealed the efficacy of PVT1, HOTAIR, NEAT1, PAI-1, and OPN as diagnostic biomarkers in BC. A year later, Levine et al [145] suggested that PVT1 exon 9 may regulate BC cell migration by reducing claudin 4 expression.…”
Section: Pvt1 In Breast Cancermentioning
confidence: 99%
“…Two contributions in this Special Issue deal with breast cancer [ 3 , 4 ], the leading cause of cancer-related death in European women. In their work, Panzetta et al [ 3 ] study how the extracellular matrix stiffness interferes in the adhesion and migration properties of two different mammary cell lines under the exposure of two different X-ray doses.…”
mentioning
confidence: 99%
“…This cellular response, called durotaxis and originally described in fibroblasts, observed in mammary cell lines reproduces the results obtained in previous experiments performed in unicellular organisms ( Dictyostelium discoideum and Caenorhabditis elegans , among others) and melanoma cell lines, as it will be mentioned elsewhere in this collection [ 5 ]. On the other hand, Levine and Ogunwobi [ 4 ] focus their work on triple-negative breast cancer, a subset of around 10% of mammary carcinomas which pursues an especially aggressive clinical course. More specifically, they have centered their research on one of the six subtypes of this tumor variant, that is, the so-called claudin-low triple-negative breast carcinoma.…”
mentioning
confidence: 99%